How many new cancer patients in Europe will require radiotherapy by 2025? An ESTRO-HERO analysis. Issue 1 (April 2016) - Borras, Josep M.; Lievens, Yolande; Barton, Michael; Corral, Julieta; Ferlay, Jacques; Bray, Freddie; Grau, Cai
Abstract: Background: The objective of this HERO study was to assess the number of new cancer patients that will require at least one course of radiotherapy by 2025. Methods: European cancer incidence data by tumor site and country for 2012 and 2025 was extracted from the GLOBOCAN database. The projection of the number of new cases took into account demographic factors (age and size of the population). Population based stages at diagnosis were taken from four European countries. Incidence and stage data were introduced in the Australian Collaboration for Cancer Outcomes Research and Evaluation (CCORE) model. Results: Among the different tumor sites, the highest expected relative increase by 2025 in treatment courses was prostate cancer (24%) while lymphoma (13%), head and neck (12%) and breast cancer (10%) were below the average. Based on the projected cancer distributions in 2025, a 16% expected increase in the number of radiotherapy treatment courses was estimated. This increase varied across European countries from less than 5% to more than 30%. Conclusion: With the already existing disparity in radiotherapy resources in mind, the data provided here should act as a leverage point to raise awareness among European health policy makers of the need for investment in radiotherapy.